1988
DOI: 10.1152/ajpendo.1988.255.6.e953
|View full text |Cite
|
Sign up to set email alerts
|

Independent stimulation of glucose metabolism and Na+-K+ exchange by insulin in the human forearm

Abstract: Insulin promotes potassium uptake into skeletal muscle by stimulating the activity of the Na+-K+ pump. To test whether insulin-induced glucose and potassium uptake are linked processes in vivo, we used the perfused forearm technique in healthy volunteers. Local hyperinsulinemia (125 +/- 11 microU/ml for 100 min) induced a net uptake of glucose and potassium (4.79 +/- 0.61 and 0.76 +/- 0.22 mumol.min-1.100 ml-1 of forearm volume, respectively). When an intra-arterial ouabain infusion (0.72 microgram.min-1.100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 23 publications
2
57
0
2
Order By: Relevance
“…In the same study [19], prevention of insulin-mediated vasodilation by direct intra-arterial infusion of an inhibitor of nitric oxide synthase, L-NMMA, reduced glucose uptake by about 35% indicating that changes in blood flow modulate glucose uptake. Using different vasoconstrictor drugs such as angiotensin II [20], norepinephrine [21], or ouabain [22], similar reductions in insulin-mediated glucose uptake have been shown supporting the notion that changes in blood flow can modulate insulinmediated glucose uptake. On the other hand, data from studies evaluating the effect of pharmacologically-increased blood flow on insulin-mediated glucose uptake are less clear.…”
Section: Insulin and The Vasculaturementioning
confidence: 74%
“…In the same study [19], prevention of insulin-mediated vasodilation by direct intra-arterial infusion of an inhibitor of nitric oxide synthase, L-NMMA, reduced glucose uptake by about 35% indicating that changes in blood flow modulate glucose uptake. Using different vasoconstrictor drugs such as angiotensin II [20], norepinephrine [21], or ouabain [22], similar reductions in insulin-mediated glucose uptake have been shown supporting the notion that changes in blood flow can modulate insulinmediated glucose uptake. On the other hand, data from studies evaluating the effect of pharmacologically-increased blood flow on insulin-mediated glucose uptake are less clear.…”
Section: Insulin and The Vasculaturementioning
confidence: 74%
“…Insulin plays an important part in ionic regulation by its stimulatory effect [11][12][13] on the Na + /K + pump. The increase in the K + levels during hyperglycaemia in protocol 1 may thus be explained by the withdrawal of that insulin, which was given to keep the study participants euglycaemic at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental work on many different tissues in vitro has shown that insulin has a stimulating effect on the Na + /K + pump [8][9][10]. In vivo, in studies in humans, this stimulatory effect on the Na + /K + pump is active at baseline insulin levels [11], and has been shown to be the cause of insulin-induced decreases in plasma K + after local perfusion of the forearm with insulin [12,13]. The stimulatory effect of insulin on the Na + /K + pump is also widely believed to underlie the hypoglycaemia-induced hypokalaemia [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, insulin may act via direct modulation of transmembrane cation exchange mechanisms. Thus, insulin has been shown to stimulate Na+/K+ATPase and the Na+/K+pump in a variety of tissues, including vascular smooth muscle [42][43][44]. Stimulation of the Na+/K+pump induces hyperpolarisation and thereby decreases calcium influx via voltage-operated channels [45].…”
Section: Discussionmentioning
confidence: 99%